2020
DOI: 10.3892/or.2020.7853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the biological functions of the prognostic genes identified by the Pathology Atlas in bladder cancer

Abstract: The prognosis-associated genes of urinary bladder cancer have been systematically investigated in the Pathology Atlas project based on The Cancer Genome Atlas data. However, the biological functions of most genes in bladder cancer remain unknown. The present study investigated the biological function of 12 of the most significant survival-associated genes ( ABRACL, MITD1, ZNF524, EMP1, HSPB6, CXorf38, TRIM38, ZNF182, ZNF195, SPRN, PTPN6 and LIPT1 ) in urothelial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Our results showed that ZNF350 expression was associated with reduced BC risk, which is consistent with previous results [ 24 ]. Similarly, another report associated high expression levels of ZNF195 with favorable survival in BC [ 25 ]. In contrast, the roles of ZNRD1, APEX2, and EBF4 in BC onset and development had not, to our knowledge, been as yet explored.…”
Section: Discussionmentioning
confidence: 90%
“…Our results showed that ZNF350 expression was associated with reduced BC risk, which is consistent with previous results [ 24 ]. Similarly, another report associated high expression levels of ZNF195 with favorable survival in BC [ 25 ]. In contrast, the roles of ZNRD1, APEX2, and EBF4 in BC onset and development had not, to our knowledge, been as yet explored.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have confirmed the critical function of HSPB6 in the endothelial proliferation and migration of various cancers [ 35 , 36 ]. Overexpression of HSPB6 suppressed BLCA T24 cell migration to a certain level but had no effect on T24 cell proliferation [ 37 ]. F-box protein 6 (FBXO6), a vital component of the ubiquitin protein ligase complex, has been reported to be involved in the invasion and sensitivity of cisplatin [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPANX family encompasses cancer-testis antigens that are epigenetically silenced in normal tissue except testes, while expressed in several human tumors (116,117). SPANXB1 has been reported to be expressed in melanoma and carcinomas of breast, lung, ovary, colon, and bladder (118)(119)(120). In TNBC, SPANXB1 has been shown to promote lung and liver metastasis and be traceable in the circulating extracellular vesicles (120).…”
Section: Discussionmentioning
confidence: 99%